Metode Pembelajaran Bahasa Arab dalam Memahami Kitab Kuning - Nurliani Yanmar; Basri Mahmud; Hamzah Hamzah (IAI Muhammadiyah Sinjai, 2023)
This study examines the use of Arabic Language Learning Method in understanding the yellow book at Santriwati Salafiyah Islamic Boarding School, Campalagian District. This type of research includes Descriptive Qualitative. The data source consists of two, namely Primary and Secondary data. The data obtained through interviews, observations and documentation are then processed through the process of data reduction, data presentation and conclusions. The results of this study show that in increasing knowledge and understanding of the yellow book in Pondok Peasantren applied several methods including the Talaqqi method, the combined method and the discussion method. The factors that become obstacles and supporters in the application of Arabic language learning are internal and external factors. Internal factors include spiritual and physical conditions while external factors include social and nonsocial environments, while supporting factors include teachers, students and curriculum.